Evaluation of the usefulness of protocol‐based pharmacist‐facilitated laboratory monitoring to ensure the safety of immune checkpoint inhibitors in patients with lung cancer. (10th June 2020) - Ikesue, Hiroaki; Kusuda, Kaori; Satsuma, Yukari; Nishiwaki, Fuki; Miura, Rieko; Masuda, Yoshio; Hirabatake, Masaki; Muroi, Nobuyuki; Fujimoto, Daichi; Morimoto, Takeshi; Tomii, Keisuke; Hashida, Tohru
Abstract: What is known and objective: Immune checkpoint inhibitors can cause immune‐related adverse events (irAEs). Improved monitoring systems for irAEs, which include laboratory tests by a qualified multidisciplinary team, might prevent patients from irAE‐associated events. Kobe City Medical Center General Hospital developed protocol‐based pharmacist‐facilitated laboratory tests named protocol‐based pharmacotherapy management (PBPM) to aid the administration of immunotherapy to patients with lung cancer. The protocol defines the laboratory test items and times at which they should be performed. It requires pharmacists to check laboratory orders initiated by physicians and enter additional test items if the orders are incomplete. We evaluated the efficacy of PBPM in irAE monitoring and compared it with those of conventional care systems. Methods: From January 2016 to March 2018, 114 patients with lung cancer received immunotherapy, which was managed by conventional care (conventional group). From April to September 2018, 62 patients were managed by PBPM (PBPM group), among those 28 patients were transited from conventional group to PBPM group. Data on whether the laboratory tests were conducted or omitted were collected retrospectively for the conventional group and prospectively for the PBPM group. Results: Within the conventional group, 4604 (87.6%) out of the 5253 laboratory test items were ordered by physicians. Of the remaining 649 test items, 224 (4.3%) items were added by physicians based on recommendations by pharmacists. However, of the 1581 (86.6%, from among 1826) test items that were previously ordered by physicians, only 231 (12.7%) test items were added by pharmacists. The execution rate was found to be significantly higher in the PBPM group (99.2% vs 91.9%, P < .001). What is new and conclusion: PBPM‐based pharmacist‐facilitated laboratory monitoring systems provided higher executing rate of laboratory order to monitor irAEs during immunotherapy. Abstract : We developed protocol‐based pharmacist‐facilitated laboratory tests named protocol‐based pharmacotherapy management (PBPM) to aid the administration of immunotherapy to patients with lung cancer. Our monitoring systems provided higher executing rate of laboratory order to monitor irAEs during immunotherapy.